Critical analysis of students’ perception on pedestrian environment in a Malaysian public university - Afsar, Bijan (2014)
During the last decade transportation in Malaysia has been changed and stepped forward into motorized-transportation. However, Malaysian government started to move toward sustainable society, which sustainable transportation is one of the parts. University Putra Malaysia’s (UPM) Serdang campus is mainly dependent on the personal cars and shuttle buses. Furthermore, routes in the campus mainly planned for the vehicles rather than pedestrians and cyclists. This study was trying to achieve two objectives: A) to document pedestrian environment physical determinants for a university campus. B) To examine physical environment factors that encourages UPM’s students to do pedestrian activities in the campus. Reviewing the literature found that four main factors (functionality, safety, aesthetics, facility) are commonly used to understand walkability of a pedestrian environment. Twenty nine attributes were also identified to be relevant and were utilized as an indicator for each of the four factors. In this study quantitative method through questionnaire survey has selected to assess the variables on a sample of subject and express the relationship between variables by using statistical calculations, such as correlations, relative frequencies, description and cross tabulation or the focus is to a large extent on the answering the research questions. Analysis indicated that students were more concern about the safety and particularly majority of the respondents reported lighting as the most important safety item of the pedestrian environment. This awareness was more significant for females in comparison to the results obtained for males. Additionally, canopy was on the top of the list as an extremely important facility that should be developed and improved. This research can be helpful for the UPM’s policy makers and master planners to facilitate in documenting pedestrian environment literature, as well as help urban designers and city planners to have a deeper perspective of pedestrian perceptions and opinions in tropical climate and particularly Malaysia.